The effect of the magnetic field on the rotation of the plane of polarization of the helium-neon laser in the optically activated water. - Uday Ameen; Evan Karromy; Abdulghafoor Abdullah (College of Education for Pure Sciences, 2009)
Abstract The aim of this paper is to study the effect of the magnetization of water on the rotation of the plane of polarization of He-Ne laser in optical active water. Firstly the magnetic water is prepared and several properties such as refractive index, absorbance, transmittance, pH and ppm are studied and compared with natural water. The effect of the magnetization of water on the rotation of the plane of polarization of laser light in optical active water is also investigated. Three samples of optical active water are prepared; optical active water, activated water and then magnetized and magnetized water and then activated by adding glucose to the water with different concentration. Verdet constant of the samples are also determined. The results of this paper show that all the properties of the magnetic water are affected by the magnetic field. The main conclusion, which is the first time to our knowledge, indicates that the sample (magnetized water and then activated) gives 18% more in the rotation of the plane of polarization of He-Ne laser in low concentration compared with activated water.